2001
DOI: 10.1097/00007890-200101270-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Endothelin Receptor Antagonist, Tezosentan, Before or After Renal Ischemia Protects Renal Function1

Abstract: The purpose of this study was to optimize the function of kidneys exposed to I/R injury. Pretreatment as well as posttreatment with Tezosentan successfully decreased Scr, increased GFR, and maintained renal architecture in kidneys after ischemia. Therefore, ET receptor antagonists may be useful to preserve renal function in the transplantation setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 18 publications
3
27
0
Order By: Relevance
“…In immunohistochemical study to determine the localization of ET-1 peptide in the postischemic kidney, an enhanced staining pattern was observed in necrotic tubular cells more markedly in NCX1 ϩ/ϩ mice than in NCX1 ϩ/Ϫ mice. When the present study was in progress, similar localization pattern of ET-1 peptide in the kidney after the ischemia and 24 h of reperfusion was demonstrated by Wilhelm et al (2001). Previously, Wilhelm et al (1999) demonstrated increased ET-1 expression in the peritubular capillary network of the kidney after ischemia.…”
Section: Acute Renal Failure and Nasupporting
confidence: 83%
“…In immunohistochemical study to determine the localization of ET-1 peptide in the postischemic kidney, an enhanced staining pattern was observed in necrotic tubular cells more markedly in NCX1 ϩ/ϩ mice than in NCX1 ϩ/Ϫ mice. When the present study was in progress, similar localization pattern of ET-1 peptide in the kidney after the ischemia and 24 h of reperfusion was demonstrated by Wilhelm et al (2001). Previously, Wilhelm et al (1999) demonstrated increased ET-1 expression in the peritubular capillary network of the kidney after ischemia.…”
Section: Acute Renal Failure and Nasupporting
confidence: 83%
“…One available evidence is that ET-1 is first expressed in increased quantities in the peritubular capillary network shortly after the onset of renal ischemia and then transported across the basement membrane of the adjacent tubular epithelial cell, which are then sloughed off during the development of acute tubular necrosis. 41) Since changes in renal ET-1 contents were parallel to those in renal venous NA levels, one might speculate that ET-1 overproduction in the post-ischemic kidney resulted from the enhanced NA release from renal sympathetic nerves. In a recent study, we found that ischemia/reperfusion-induced ARF was attenuated by a surgical or pharmacological blockade of renal sympathetic nerve, followed by a suppression of elevated renal venous NA levels.…”
Section: Discussionmentioning
confidence: 98%
“…This agent is a substrate for ET␣ receptors, found on Ito cells, and ET␤ receptors, found on endothelial cells and Kupffer cells. 107 In rats given tezosentan before reper- fusion, serum glutamic oxaloacetic transaminase release was significantly lower, and at 24 hours, histology was markedly improved over that of controls. There was also a reduction in chemokines (interleukin-1␤ and MIP-2) released from the Kupffer cells.…”
Section: Experimental Strategies For the Manipulation Of Marginal Donorsmentioning
confidence: 97%
“…There was also a reduction in chemokines (interleukin-1␤ and MIP-2) released from the Kupffer cells. 107 Soluble forms of the adhesion molecule receptor blockers prevent neutrophils and platelets from adhering to endothelial cell surface. Brain death increases sensitivity to IR injury and CIT and may contribute to immunogenicity.…”
Section: Experimental Strategies For the Manipulation Of Marginal Donorsmentioning
confidence: 99%